On IPv6 Slow Adoption; Why We Might Approach it Wrongly? - Mukhammad Andri Setiawan (Universitas Ahmad Dahlan, 2023)
The slow adoption of IPv6, despite its numerous advantages over IPv4, is a pressing issue in many regions, including Indonesia. This challenge is particularly significant given the increasing demand for Internet of Things (IoT) devices and the need for a sustainable, scalable, and flexible network infrastructure. In response to this issue, our research introduces the Design Thinking-Inspired Technology Adoption (DTITA) model. This innovative approach leverages design thinking principles to facilitate the adoption of new and challenging technologies. DTITA incorporates the five stages of design thinking alongside traditional technology adoption factors, such as perceived usefulness, ease of use, and social influence. The DTITA model aims to create user-centric solutions that address new technologies' unique challenges and barriers. By placing the user at the center of the design process, we were able to develop solutions that are not only technologically advanced but also highly accessible and relevant to users. Through a survey involving individuals from the education industry, Internet Service Providers (ISPs), content providers, government institutions, and the Information and Communication Technology (ICT) industry, we identified key barriers impeding the widespread implementation of IPv6. This study provides valuable insights into the application of design thinking in the context of technology adoption, particularly in the case of IPv6. It contributes to the broader discourse on technology adoption and offers practical recommendations for stakeholders and decision-makers in Indonesia.